PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MATERI SIFAT-SIFAT BANGUN DATAR DENGAN PENDEKATAN SAINTIFIK UNTUK SISWA KELAS V SEKOLAH DASAR - Erif Ahdhianto (Universitas PGRI Yogyakarta, 2016)
Curriculum 2013 is currently using the scientific approach which curriculum accentuate dimensional observation, reasoning, discovery, validation, and an explanation of the truth. To accommodate this, the developed mathematical learning tools with the scientific approach. This study aims to describe the development process and produce good math learning tools to math instruction material properties of flat wake up with a scientific approach to the fifth grade of elementary school students that includes lesson plans, worksheets, and THB because these three components is the most important component in the learning which must be designed by the teacher as a guide in achieving the desired learning objectives. Software development model used in the study is a general education development model of Plomp (1997) which consists of several phases, namely: (1) the initial investigation phase, (2) the design phase, (3) the realization phase, and (4) the test phase, evaluation, and revision. Tests conducted research at Citrus Elementary School fifth grade students 2 Lakarsantri Surabaya as many as 12 students. Research instruments used include the validation sheets, observation sheets, and student questionnaire responses to mathematics learning material properties build flat wake up with a scientific approach. Data on the validity of the device obtained from validation sheet. The results obtained from the third validator, a learning device be valid and quite valid, and can be used with little revision. Data about the practicality of the device is obtained from the feasibility RPP sheet. The results of feasibility analysis RPP during two meetings in learning to be in either category. Obtained data on the effectiveness of student activities, student responses, and THB. Every aspect of the learning activities of students in achieving the criteria limits the effectiveness, including the responses of students in learning in a positive category with a percentage of 70%, and THB declared effective because 80% of students scored a minimum standard so that THB can completeness be used to measure student mastery of the material.